APPLICATION OF AQUAPONIC TECHNOLOGY IN GAPOKTAN BINA SEJAHTERA, AN EFFORT TO IMPROVE FOOD SECURITY - Nani Yulianti; Arifah Rahayu; Yuliawati Yuliawati; Nur Rochman; Setyono Setyono; Yanyan Mulyaningsih; Oktavianus LT; Muhamad Zainal Fanani; Fia Sri Mumpuni; Yudi Wahyudin; Mulyana Mulyana; Ekorini Farastuti; Dudi Lesmana (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Aquaponics is an integration between fish and plant cultivation that benefits these two sectors. The development of aquaponics at the farm level can be an effort to increase food security. This community service activity aims to apply aquaponic leaf vegetable cultivation techniques, to optimize the facilities available at Gapoktan Bina Sejahtera (fish ponds). Activities carried out by counseling methods, training and demolots to farmers regarding the cultivation techniques of leaf vegetables and red tilapia with an aquaponic system. During the activity, monitoring was also carried out by a team of service lecturers, assistance by student teams and evaluation through pretest and posttest. This community service activity is able to provide new experiences, and increase farmers' knowledge and skills in cultivating red tilapia and leaf vegetables with an aquaponic system.